PENGARUH KARAKTERISTIK DEWAN PENGAWAS SYARIAH, PROFITABILITAS, UKURAN PERUSAHAAN DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Arafah, Monalisa Dinda; Fakhruddin, Iwan; Pramono, Hadi; Santoso, Selamet Eko Budi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to examine the influence of sharia supervisory board characteristics, profitability, company size and audit quality on earnings management. The population in this research is Sharia Commercial Bank (BUS) companies registered with the Financial Services Authority (OJK) in 2016-2022. This research analyzes secondary data which is called quantitative research. The sample in this study was selected using a purposive sampling, and 92 samples were obtained from 14 companies. This research tests the hypothesis using multiple regression analysis. The results of this research indicate that DPS size, cross-member DPS, profitability and audit quality have no influence on earnings management. The number of DPS meetings and company size have a negative effect on earnings management.